Condensed Tannins in Sainfoin: Composition, Concentration, and Effects on Nutritive and Feeding Value of Sainfoin Forage. Issue 1 (1st January 2015) - Wang, Yuxi; McAllister, Tim A.; Acharya, Surya
ABSTRACT: Legume forage is the most economical source of nutrients for ruminants. Sainfoin ( Onobrychis viciifolia Scop.) is high nutritive forage growing worldwide and possesses polyphenolics including condensed tannins (CT) that contribute to some of its superior nutritional properties such as improved protein utilization, bloat‐free, and anthelmintic characteristics. This review attempts to capture the latest research in characterizing the impact of polyphenolics on the feeding value of sainfoin with an emphasis on CT. Sainfoin contains a diverse array of polyphenolics and its CT content declines as the plant matures, with an increase in the degree of polymerization and a decreasing proportion of prodelphinidins, resulting in a reduction in biological activity. This forage is best to be utilized between bud to flowering stage to balance the biological activity of CT and biomass yield. Incorporation of sainfoin into alfalfa ( Medicago sativa L.) pasture has been effective in reducing alfalfa pasture bloat due to the presence of CT. New sainfoin populations suitable for survival in high‐performance grazing systems have been developed and have demonstrated superior anti bloat activity due to the increased grazing persistence. Fresh sainfoin is the best feed for cattle for maximum effect of CT, but if it needs to be preserved then hay would be better than silage in terms of preservation of the biological activity of CT. Although greater CT content is desirable for this forage in terms of antibloat and antiparasitic activity, sainfoin with CT concentration at about 50 g kg −1 dry matter (DM) offer the best feed value.